Amorphous molybdenum sulfide quantum dots: an efficient hydrogen evolution electrocatalyst in neutral medium. Issue 40 (22nd September 2016) - Dinda, Diptiman; Ahmed, Md. Estak; Mandal, Sumit; Mondal, Biswajit; Saha, Shyamal Kumar
Abstract : Chemically synthesized amorphous MoS x quantum dots show excellent HER activity in neutral medium during 12 h of electrolysis. Abstract : To overcome the limitations of active edges, electrical conductivity and the surface area of MoS2 nanosheets, in the present work, we have successfully synthesized amorphous MoS x quantum dots with a larger number of edge atoms using a simple chemical reaction via a bottom-up approach. Structural and chemical characterizations are carried out by TEM, XRD, Raman and XPS measurements. XPS and EDX analyses indicate a larger number of unsaturated 'S' atoms in these ultrafine amorphous quantum dots. We have used this material as an efficient electrocatalyst for the hydrogen evolution reaction (HER) in neutral medium. The material shows a remarkably low overpotential (65 mV) towards HER compared to that of other crystalline MoS2 quantum dots or nanomaterials. The origin of such a low onset potential is the presence of more unsaturated sulfur (S2 2− ) ligands and enhanced active edge sites. It also shows very high catalytic activity as well as good stability after 12 h of hydrogen generation in neutral water medium.